Antibacterial Properties and Computational Insights of Potent Novel Linezolid-Based Oxazolidinones - M. Shaheer Malik; Shaikh Faazil; Meshari A. Alsharif; Qazi Mohammad Sajid Jamal; Jabir H. Al-Fahemi; Amrita Banerjee; Arpita Chattopadhyay; Samir Kumar Pal; Ahmed Kamal; Saleh A. Ahmed (MDPI AG, 2023)
The mounting evidence of bacterial resistance against commonly prescribed antibiotics warrants the development of new antibacterial drugs on an urgent basis. Linezolid, an oxazolidinone antibiotic, is a lead molecule in designing new oxazolidinones as antibacterial agents. In this study, we report the antibacterial potential of the novel oxazolidinone-sulphonamide/amide conjugates that were recently reported by our research group. The antibacterial assays showed that, from the series, oxazolidinones 2 and 3a exhibited excellent potency (MIC of 1.17 μg/mL) against B. subtilis and P. aeruginosa strains, along with good antibiofilm activity. Docking studies revealed higher binding affinities of oxazolidinones 2 and 3a compared to linezolid, which were further validated by molecular dynamics simulations. In addition to this, other computational studies, one-descriptor (log P) analysis, ADME-T and drug likeness studies demonstrated the potential of these novel linezolid-based oxazolidinones to be taken forward for further studies.